Digitalisasi Visual Identity Padang Old Town Resto Gallery - Usman, Robby; Setiawan, Berlina (Jurnal Sains Informatika Terapan, 2022)
Culinary development in Padang city is growing rapidly for the past few years, there are so many cafes an restaurants have emerged especially in tourist attraction, Padang Old Town. Padang Old Town Resto Gallery serves varied foods and has a concept of combining Dutch-era architectural design and Chinese culture. However, the visual identity of Padang Old Town Resto Gallery has not been clearly described. The visual identityof Padang Old Town Resto Gallery is needed so the restaurant could be easily recognized and could attract the target audience. This research uses SWOT method, collecting data using observations and interviews, and distributing questionnaires whether the visitors can identify visual identity of Padang Old Town Resto Gallery. Itis expected that Padang Old Town Resto Gallery can create and implement the visual identity, so it can improvethe restaurant’s image among the visitors.